SPEECH ACTS ON COMPANY’S PRESENTATION IN GERMAN FOR BUSINESS AND ECONOMICS - Hutabarat, Mery Dahlia (Indonesian Journal of Applied Linguistics, 2015)
The research is aimed to analyze text presentations  of company‘s profile and its products. It is included under Wirtschaftsdeutsch or ‘German for Business and Economics’. The analysis of sentences and the elements contained in the text presentation of 14 companies refers to the theories of speech act analysis by various experts in linguistics such as Austin, Searle and Engel. The functions of sentence‘s elements are studied based on the theory of dependency grammar put forward by Engel. There are 85 sentences for data. The results swho that speech acts dominating the text presentation of company’s profile is notification in a narrow sense that is exercitation and refers to the interlocutor as hearer. The dominating elements in the sentences of the company‘s profile presentations under research are subjects and Akkusativergänzungen (indirect object). Product presentations are dominated by nominal phrases.